METTL14 alleviates heat stress in Hu sheep involves enhancing fatty acid oxidation while reducing lipid deposition - Chen, Bowen; Yuan, Chao; Guo, Tingting; Sun, Lixia; Liu, Jianbin; Lu, Zengkui (Frontiers in Veterinary Science, 2026)
ObjectiveHeat stress significantly compromises sheep production performance, product quality, and overall health, leading to increased management costs and reduced profitability. Previous studies from our group demonstrated that the m6A methyltransferase gene METTL14 is involved in both the heat stress response and the regulation of lipid metabolism in Hu sheep, suggesting a potential role in mediating heat stress through hepatic metabolic control. However, the specific mechanisms by which METTL14 regulates heat stress and lipid metabolism, as well as the functional linkage between these processes, remain poorly understoodMethodsWe first established heat stress (HS), lipid deposition (LD), and lipid deposition heat stress (LDHS) models in Hu sheep hepatocytes and adipocytes. By interfering with and overexpressing the METTL14 in these models, techniques such as qRT-PCR, immunofluorescence, RNA-seq, and LC-MS were employedResultsWe found that METTL14 contributes to the heat stress response under heat stress, suppresses the expression of heat shock-related genes, and significantly modulates lipid metabolism pathways. Under combined conditions of lipid accumulation and heat stress, METTL14 participated in the lipid deposition process and downregulated the expression of associated genes. Furthermore, overexpression of METTL14 under these conditions increased m6A methylation levels, downregulated heat shock genes (HSP60, HSP70, HSP110) and key lipogenic genes (FABP4, PPARγ, Accα). Notably, elevated expression of MTTP enhanced triglyceride export, ultimately reducing intracellular triglyceride content.ConclusionIn summary, this study unveils a novel mechanism through which METTL14 mitigates heat stress in Hu sheep-by promoting fatty acid oxidation and attenuating lipid deposition.